KONSTRUKSI KESALIHAN SEBAGAI PENEGUHAN DOMESTIKASI PEREMPUAN DALAM TAFSIR AUDIOVISUAL (ANALISIS KONTEKSTUALISASI QS. AN-NISA’ AYAT 34 DALAM INTERPRETASI YUFID.TV) - Sofiyatus Soleha; Ifadah Ifadah; Haizumiah Haizumiah (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
Until now on, women are still constructed as weak creatures and behind men. This is because the developing culture in our society has a very strong patriarchal side, where restricting the women’s movements in expressing themselves. In addition, existing religious doctrines also lead to the discourse that women who are outside the home deviate from Islamic law. This restriction of women's actions is often based on embedding the identity of women’s piety (salihah). One of them is done by Yufid.TV in his interpretation of QS. An-Nisa: 34 that a salihah is a woman who obeys her husband and stays at home. This paper is a netnographic study of women's piety discourse on Indonesian social media. So the transcendent focus in this study is to unravel how the discourse of women's piety is shaped by Yufid.TV through its interpretation of QS. An-Nisa': 34. Next, contextualize the verse by reviewing its relevance to the issues brought to the contemporary context. Using descriptive-critical analysis, this study shows that the discourse of piety is formed through its understanding of QS. An-Nisa': 34 comes to the meaning that women are responsible for obeying and serving their husbands, so they must be in the house. The construction is believed to be a form of textual understanding of the Qur’an. So that, this piety discourse reflects on the patriarchal mindset, they are an attempt to make the existence of women in the domestic sector only.